PENANAMAN KARAKTER RELIGIUS PADA SISWA SD AL ISLAM MELALUI BUDAYA SEKOLAH - Hafizah, Meilani; Zumrotun, Erna (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
This study aims to analyze how the implementation of religious character education through school culture at Al Islam Elementary School. The subjects in this study were students in grades 1A and 4A. This research uses a qualitative method with a case study approach with qualitative data analysis stages including data reduction, data presentation, and conclusion drawing. Data collection was obtained through observation, interviews, and documentation. The results showed that school culture activities at Al Islam Elementary School using the habituation method have a series of activities such as the 5S culture, reading asmaul husna and prayers, congregational prayers, istighosah, Friday charity, and cleaning classes. This activity aims to form the next generation of the nation who are not only superior in the academic field but also have good and commendable morals. Supporting factors in the implementation of these activities include the role of the principal and teachers as role models for students, qualified and competent human resources, adequate school facilities, integrated in learning. However, there are challenges faced such as unruly students and bad influences from the environment outside the school. Mutual cooperation, coordination with parents of students is the right solution for the sustainability of planting religious characters through school culture at Al Islam Elementary School.